Ecofisiologia da germinação e do crescimento inicial de Piptadenia stipulacea (Benth.) Ducke E Anadenanthera colubrina (Vell.) Brenan - Ferreira, Wanessa Nepomuceno (2011)
This study presents the hypothesis that P. stipulacea is a species characteristic of early stages of succession, while A. colubrina in later stages. To characterize the two species studied are some attributes used in classification of ecological groups of tropical rainforests, answering the following questions: a) species have seed dormancy? b) what conditions of temperature and light for germination? c) the seeds are desiccation tolerance? d) the characteristics of seedling growth under different levels of irradiance? Thus, the work made the following predictions: a) seeds of P. stipulacea present dormancy, while those of A. colubrina not present; b) seeds of P. stipulacea germinate over a wide temperature range, while those of A. colubrina germinate in a narrow temperature range; c) the seeds of P. stipulacea tolerate low levels of desiccation, while those of A. colubrina not tolerate; d) seedlings of P. stipulacea grow best at higher irradiance levels, while those of A. colubrina grow best at lower levels of irradiance. Fruits were collected in the caatinga area located on the farm "Não Me Deixes” city of Quixada-CE, and the experiments were performed at the Seed Analysis Laboratory and the Core Teaching and Research in Urban Agriculture. Results of preliminary testing of germination showed that seeds of P. stipulacea present dormancy and are better solved with chemical scarification for 10 minutes. The seeds of A. colubrina have no dormancy. The experiment temperature and light was revealed that the two species have the same range of germination (10°C to 40ºC), with best germination at 30°C, but at lower temperatures P. stipulacea showed germination very low. As for tolerance to desiccation, seeds of P. stipulacea bore drying up 5.16% moisture without influencing germination, representing orthodox behavior. Already A. colubrina germination decreased as the seeds lost water, but even with a water content of 5.81%, germination remained above 80%, indicating that this species also has orthodox seeds. In the irradiance experiment, seedlings of P. stipulacea showed larger diameter in full sun, and all treatments accumulated more biomass to the stem. A. colubrina showed greater height and diameter in 50% shade and a larger number of leaves and shoot biomass by 70% shade, indicating that this species tolerates intermediate levels of shade. It is suggested that features used for classification of ecological groups of tropical forests could also be used to support the identification of which stage of succession belongs to certain species of caatinga, with the aim of understanding their occurrence, distribution and development, for better conservation and use suitable for the reforestation of degraded areas.